2021
DOI: 10.1002/navi.454
|View full text |Cite
|
Sign up to set email alerts
|

Study of structures of the sporadic E layer by using dense GNSS network observations

Abstract: The sporadic E (Es) layer has been known to introduce long-range propagation of aeronautical very high frequency (VHF) navigation beyond the radio horizon and cause potential interference on the navigation system. This study utilizes a rate of total electron content (TEC) index (ROTI) map with dense Global Navigation Satellite System (GNSS) observations for effective Es layer detection. The daytime Es layer shows a well-defined frontal structure when ROTI values are mapped at the typical Es layer height (100 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…ROTI values are estimated for each GPS satellite and GEONET receiver pairs and mapped at the IPPs at an altitude of 350 km. ROTI maps are generated every 5 min in near real-time with 2-min latency (Saito et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…ROTI values are estimated for each GPS satellite and GEONET receiver pairs and mapped at the IPPs at an altitude of 350 km. ROTI maps are generated every 5 min in near real-time with 2-min latency (Saito et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Saito et al. (2021) showed that bottom side of the front‐like Es layer appeared to have wavy structure which is steep on the front side and gentle in the tail side by network observations of the total electron content and its fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other causes of fluctuations in propagation path such as tropospheric refractivity variation should also be examined. Statistical analysis of the EsAP of the ILS LOC signals and comparison with other observations such as GNSS network observation (Saito et al., 2021) and EsAP network observation (Hosokawa et al., 2021) and with numerical simulation (Andoh et al., 2020) are necessary and left for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RO-observed Es layers from COSMIC and Fengyun-3C (FY-3C) missions were intercompared globally and found to be consistent, though, with slight differences (Xu et al 2022). In addition, Saito et al (2021) identified fine structures (such as the sub-structures in the Es layer front) by utilizing total electron content (TEC) index (ROTI) maps with dense Global Navigation Satellite System (GNSS) observations over Japan.…”
Section: Introductionmentioning
confidence: 99%